Epigenetic and post‐transcriptional regulation of somatostatin receptor subtype 5 (SST5) in pituitary and pancreatic neuroendocrine tumors. Issue 3 (26th October 2021) - Pedraza‐Arevalo, Sergio; Ibáñez‐Costa, Alejandro; Blázquez‐Encinas, Ricardo; Branco, Miguel R.; Vázquez‐Borrego, Mari C.; Herrera‐Martínez, Aura D.; Venegas‐Moreno, Eva; Serrano‐Blanch, Raquel; Arjona‐Sánchez, Álvaro; Gálvez‐Moreno, María A.; Korbonits, Marta; Soto‐Moreno, Alfonso; et al.
Abstract : Somatostatin receptor subtype 5 (SST5 ) is an emerging biomarker and actionable target in pituitary (PitNETs) and pancreatic (PanNETs) neuroendocrine tumors. Transcriptional and epigenetic regulation of SSTR5 gene expression and mRNA biogenesis is poorly understood. Recently, an overlapping natural antisense transcript, SSTR5‐AS1, potentially regulating SSTR5 expression, was identified. We aimed to elucidate whether epigenetic processes contribute to the regulation of SSTR5 expression in PitNETs (somatotropinomas) and PanNETs. We analyzed the SSTR5 / SSTR5‐AS1 human locus in silico to identify CpG islands. SSTR5 and SSTR5‐AS1 expression was assessed by quantitative real‐time PCR (qPCR) in 27 somatotropinomas, 11 normal pituitaries (NPs), and 15 PanNETs/paired adjacent (control) samples. We evaluated methylation grade in four CpG islands in the SSTR5 / SSTR5‐AS1 genes. Results revealed that SSTR5 and SSTR5‐AS1 were directly correlated in NP, somatotropinoma, and PanNET samples. Interestingly, selected CpG islands were differentially methylated in somatotropinomas compared with NPs. In PanNETs cell lines, SSTR5‐AS1 silencing downregulated SSTR5 expression, altered aggressiveness features, and influenced pasireotide response. These results provide evidence that SSTR5 expression in PitNETs and PanNETs can be epigenetically regulated by the SSTR5‐AS1 antisense transcript and, indirectly, by DNA methylation, which may thereby impact tumor behavior and treatment response. Abstract : Somatostatin receptor subtype 5 (SST5 ) is a key player in neuroendocrine tumors (NETs). Yet, its regulation is still insufficiently understood. This study presents original evidence that SSTR5 expression may be epigenetically regulated by the SSTR5‐AS1 antisense transcript and DNA methylation in pituitary and pancreatic NETs, providing a new regulatory layer influencing receptor levels and, thereby, tumor behavior and treatment response.